Syntax Tools of General Denial in French (Eurasian Journal of Learning and Academic Teaching, 2023)
This article is a French syntax tool dedicated to studying one of the most relevant and controversial topics: the meaning of denial, the legalization of meaning are their pieces of denial and they are located the place, the meaning of the vocabulary of the vocabulary, the vocabulary of the vocabulary.